Chlorinated Very Short-Lived Substances : Modelling their global emissions and impact on stratospheric ozone - Claxton, Tom (Lancaster University, 2021)
Since the discovery of the damaging effects of chlorofluorocarbons, stratospheric ozone has been studied extensively in the last 50 years. While the Montreal Protocol and amendments have largely nullified the threat from long-lived ozone-depleting gases, emerging evidence suggests uncontrolled chlorinated compounds, Very Short-Lived Substances (Cl-VSLS), present a barrier to timely ozone recovery. This thesis extends scientific understanding of Cl-VSLS emissions and impacts, combining observations, inversion methods and a 3-D chemistry transport model. This work calculates policy-relevant ozone depletion potentials (ODPs) of four Cl-VSLS (CH2Cl2, CHCl3, C2Cl4, C2H4Cl2) using a troposphere-stratosphere modelling system. The influence of emission location and season on the ODPs is investigated. Whilst little seasonal variability exists, the location of emissions exerts a strong influence, with the largest ODPs due to Tropical Asian emissions. Chloroform (CHCl3) and dichloromethane (CH2Cl2) have the largest ODPs (up to ~0.02-0.03), comparable to some long-lived halocarbons restricted by the Montreal Protocol. A synthesis inversion is used to calculate regional Cl-VSLS fluxes based on minimising differences between modelled and observed abundances with prior constraints. Over 2007-2017, global CH2Cl2 emissions increase significantly due to increasing Asian emissions, while C2Cl4 emissions decrease, from diminishing uses in Europe and North America. The emissions are evaluated and provide a good match to assimilated observations and those independent to the inversion. Stratospheric impacts of Cl-VSLS are investigated using time-varying emissions. The stratospheric input of chlorine from Cl-VSLS and products increased by 43% between 2007 and 2017, from 92.3 ± 5.0 ppt Cl to 132.1 ± 8.9 ppt Cl. Stratospheric model simulations show marked decrease in lower stratospheric ozone due to Cl-VSLS. In 2017, over Antarctica, Cl-VSLS reduced lower stratospheric ozone by 1.2% and the global mean column reduction was 0.4% (-1.2 DU). Increasing Asian emissions indicate potential for greater future impacts. Hence, Cl-VSLS should continue to be monitored.